Dosimetric parameters associated with radiation-induced esophagitis in breast cancer patients undergoing regional nodal irradiation. (February 2021) - Yaney, Alexander; Ayan, Ahmet S.; Pan, Xueliang; Jhawar, Sachin; Healy, Erin; Beyer, Sasha; Lindsey, Kylee; Kuhn, Karla; Tedrick, Kayla; White, Julia R.; Bazan, Jose G.
Highlights: We found that >15% of RNI patients developed symptomatic esophagitis. IMRT use was associated with higher rates of esophagitis. The esophagus OAR was systematically contoured from cricoid to carina. We propose these esophageal OAR constraints: mean <11 Gy, V10 <30%, and V20 <15%. Abstract: Background/Purpose: Rates of acute esophagitis in breast cancer patients undergoing regional nodal irradiation (RNI) are under-reported. We set to identify esophageal dose–volume constraints associated with grade 2 esophagitis (G2E). We hypothesized that the G2E rate was higher with intensity modulated radiation therapy (IMRT) vs. 3D conformal radiation therapy (3DCRT). Materials/Methods: We identified patients that received RNI (50 Gy/25 fractions) from 1/2013 to 6/2019. We retrospectively contoured the esophagus in a consistent manner and recorded esophageal mean dose, max dose, and V10–V50. Our primary endpoint was the G2E rate. Receiver operating characteristics curves analysis (e.g., Youden's J statistic) were used to determine the cutpoints for the dosimetric parameters which were then tested in logistic regression models. Results: We identified 531 patients (50% left-sided; 41% IMRT; 16.2% G2E). G2E was significantly higher in IMRT vs. 3DCRT patients (23.6% vs. 10.9%, p < 0.0001). All esophageal dosimetric parameters were significantly associated with G2E after adjusting for age and laterality. The cutpoints for esophageal mean dose, V10 and V20 were 11 Gy, 30%, and 15%, respectively. The associations between the dichotomized dose–volume parameters and G2E were OR = 3.82 (95% CI 2.28–6.40, p < 0.0001) for esophageal mean dose, OR = 5.37 (95% CI 3.01–9.58, p < 0.0001) for esophageal V10, and OR = 3.23 (95% CI 1.93–5.41, p < 0.0001) for esophageal V20. Conclusion: In patients receiving RNI with modern techniques, we found that G2E occurs in >15%, and more frequently with IMRT. These data strongly support the routine contouring of the esophagus in RNI planning, and our constraints should be incorporated in future prospective protocols of RNI.